Generation of Adaptive Immune Responses Following Influenza Virus Challenge is Not Compromised by Pre-Treatment with the TLR-2 Agonist Pam2Cys - Mifsud, Edin Jessica; Tan, Amabel C. L.; Brown, Lorena Elizabeth; Chua, Brendon Yew Loong; Jackson, David C. (Frontiers in Immunology, 2015)
Immunostimulatory agents provide a new category of anti-microbial agents that activate the host’s innate immune system allowing control of viral and/or bacterial infections. The TLR-2 agonist PEG-Pam2Cys has been shown to mediate potent anti-viral activity against influenza viruses when administered prophylactically (Tan et al., 2012). Here we demonstrate that treatment of mice with PEG-Pam2Cys does not compromise their ability to generate adaptive immune responses following subsequent challenge with influenza virus. The antibody induced in mice pre-treated with Pam2Cys possessed hemagglutination-inhibiting activities and the CD8+ T-cell responses that were elicited provided protection against heterologous viral challenge. In the absence of an effective influenza vaccine, an agent that provides immediate protection against the virus and does not compromise the induction of influenza-specific immunity on exposure to infectious virus provides an opportunity for population immunity to be achieved through natural exposure to virus.